Women and Animals in Anita Desai’s Fire on the Mountain: A Study of Violence - Neupane, Ravindra (Ganeshman Darpan, 2023)
This paper examines the novel Fire on the Mountain by Anita Desai within the context of materialist postcolonial ecofeminism. Despite the fact that both women and animals are excluded from society, I contend that the "other" in the shape of both women and animals is the focus of the book. Through the story, the author reframes topics like women and animals which are typically discussed through the male perspective. The woman serves as the interpreter between humans and animals. The animal figure is used to mediate self-politics and relationships between the two sexes. I demonstrate the significance of the ambivalent viewpoint when discussing the novel’s protagonists. These ladies do not fall into either the cultural or natural domains in the culture-nature dichotomy. They demonstrate their ambivalence about both the culture/nature notions by straddling the binary in-between. No demeaning romantic or celebratory association exists between women and the natural world or with animals. The issue of violence against both women and animals has been looked at within this paradigm.